The use of antimicrobial drugs in children’s surgical departments according to the results of the Point prevalence study - Serednia , Roksolana; Khaitovych , Mykola; Kysil , Nadiia; Zabrotska , Julia; Temirova Оlena; Kysil , Denys (The Ukrainian Scientific Medical Youth Journal, 2023)
the use of antimicrobial drugs is of great importance in surgical practice, as they can affect microorganisms that are frequent causative agents of surgical wound infections. In the department of surgery, the preferable use of antimicrobial drugs is during the perioperative prevention period or treatment of infectious diseases. However, the data on the use of antimicrobial drugs indicates their irrational and extensive administration, which results in the emergence of antimicrobial resistance. For efficient prevention of antimicrobial resistance in healthcare institutions, programs for the administration of antimicrobial drugs are being implemented. The study aimed to assess the appropriate use of antimicrobial drugs in the departments of pediatric surgery. A point prevalence survey was conducted in 4 surgical units of 2 teaching hospitals (the use of antimicrobial drugs on 32 children aged 5 months to 17 years was reviewed). Most (60 %) of the children with age ranging from 7 to 14 years old. Children were in departments of pediatric surgery with various diagnoses, most commonly children with chronic osteomyelitis (16 %) and acute appendicitis (9 %). It was established that in 32 % of the cases, antimicrobial drugs were used for perioperative antibiotic prophylaxis, and in 68 % – for treatment. For perioperative prophylaxis, cefuroxime, a cephalosporin antibiotic of the Ⅱ generation, was used more often (70 %), and ceftriaxone was used in others. For antimicrobial therapy, monotherapy was used on 71.4 % of the patients, in particular, on 46.7 % – with an antibiotic of the Ⅲ generation cephalosporin group – ceftazidime. 28% of children used combined therapy of two or more antibacterial drugs. Therefore, according to the Point prevalence study in children’s surgical departments, perioperative prophylaxis is carried out with 2nd and 3rd-generation cephalosporin drugs, in most cases monotherapy is used for treatment, and the most used drug is ceftazidime.